The Effectiveness of Discovery Learning-Based Biodiesel Production Practice in Improving Students’ Creative Thinking Skills on Renewable Energy Subject Matter - Faisal, Nur Zamzam Yuniar; Dadan Rosana; Insih Wilujeng; Laifa Rahmawati (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to determine the effectiveness of biodiesel production practice in enhancing the creative thinking skills of eighth-grade students at junior high school in Sleman in the renewable energy topic. The research employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 25 students selected purposively from one class. The instrument used was a creative thinking skills test covering indicators of flexibility, fluency, originality, elaboration, and sensitivity to problems. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, n-Gain calculation, and effect size measurement. The results showed an improvement in students’ creative thinking skills with a medium category n-Gain and a very large effect size (1.84), along with a significant difference between pretest and posttest scores (p < 0.05). The biodiesel production practice proved effective in developing students’ creativity. This study provides important implications for developing practical-based learning methods that are relevant to environmental and renewable energy issues.